Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 191477 by Spillover last updated on 24/Apr/23

Prove that    ((tan y+sec y−1)/(tan y−sec y+1))=tan y+sec y

Provethattany+secy1tanysecy+1=tany+secy

Answered by ARUNG_Brandon_MBU last updated on 24/Apr/23

((tanx+secx−1)/(tanx−secx+1))=((sinx+1−cosx)/(sinx−1+cosx))  =((2sin(x/2)(cos(x/2)+sin(x/2)))/(2sin(x/2)(cos(x/2)−sin(x/2))))×((cos(x/2)+sin(x/2))/(cos(x/2)+sin(x/2)))  =((1+2sin(x/2)cos(x/2))/(cos^2 (x/2)−sin^2 (x/2)))=((sinx+1)/(cosx))=tanx+secx

tanx+secx1tanxsecx+1=sinx+1cosxsinx1+cosx=2sinx2(cosx2+sinx2)2sinx2(cosx2sinx2)×cosx2+sinx2cosx2+sinx2=1+2sinx2cosx2cos2x2sin2x2=sinx+1cosx=tanx+secx

Terms of Service

Privacy Policy

Contact: info@tinkutara.com